(untitled) (Environment & Health, 2021)
The analysis of the documents of the authoritative international organizations and scientific works was carried out from the point of view of the development of the strategy for ensuring the radiation quality of drinking water. The radiation parameters of the quality of drinking water, the interpretation of monitoring results by screening and recommended levels, the value of the individual dose criterion, as well as algorithms for establishing the frequency of monitoring of the radiation parameters of drinking water were considered. Objective: We analyzed the documents of reputable international organizations and scientific works in terms of the development of the strategy for ensuring radiation quality of drinking water and the features of the practical application of the parameters of water radiation quality in the world and Ukraine. Methods: bibliographic, analytical. Materials: We performed the analysis of the documents of international organizations (WHO, IAEA, ICRP, UNSCEAR), as well as scientific publications on the radiation quality of drinking water in the light of the experience in measuring the content of drinking water radionuclides at the territory of Ukraine. Results: Materials of the international documents and scientific publications demonstrate that the assessment of radiation quality of drinking water requires a balanced analysis. In some cases, based on the results of only one determination of the total alpha and total beta activity, it is impossible to draw an unambiguous conclusion about the suitability or unsuitability of drinking water for consumption. Taking into account the geological heterogeneity of the territory of Ukraine, in order to obtain sufficient data on the radioactivity of groundwater, it is necessary to conduct extensive screening studies of the radiation quality of water in the regions of the country with the involvement of geological and monitoring services, local authorities.